Chylothorax in a patient with advanced ovarian cancer: a case report and literature review - Wang, Qiuying; Zhang, Xiaolan; Niu, Ke; Shen, Wenjie (Frontiers in Oncology, 2025)
BackgroundOvarian cancer complicated with chylothorax is extremely rare, and only eight papers can be searched in PubMed. We report a case of advanced ovarian cancer with extensive lymphatic metastasis that led to chylothorax and then chylous ascites. Combined with the literature review, we try to identify its clinical characteristics.Case descriptionA 64-year-old patient with advanced ovarian cancer relapsed, presenting with extensive lymphatic metastasis and a right pleural effusion. Thoracentesis was performed. The drainage fluid had a milky white appearance with triglyceride levels >1.24 mmol/L (110 mg/dL), a cholesterol level <5.18 mmol/L (200 mg/dL), and a positive chyle test. A multi-disciplinary team recommended anti-tumor therapy for ovarian cancer and conservative treatment of chylothorax, including a strict diet with low-fat medium–long-chain triglycerides and chest tube insertion with interleukin-2 intrapleural perfusion as the pleurodesis agent. Chylothorax improved significantly with progressively reduced and transparent pleural effusion. However, strict diet control affected her quality of life negatively, and the patient was not able to adhere to the diet plan. Therefore, chylothorax recurred, but chyle was produced slowly; thoracentesis was performed repeatedly with IL-2 or cisplatin pleural perfusion at intervals of 2–5 months (a total of six times) in March 2021–June 2023. In June 2023, the patient was not able to tolerate systemic chemotherapy because of severe myelosuppression after fourth-line chemotherapy. The patient developed bilateral chylothorax and then chylous ascites in December 2023. Finally, the patient died in March 2024.ConclusionOvarian cancer complicated with chylothorax is a rare condition with a relatively poor prognosis. Pleural fluid analysis can identify this condition when clinical suspicion exists. Anti-tumor treatment of ovarian cancer and conservative management of chylothorax were first recommended instead of surgery, which have been proven to be effective in treating OCC.